2020
DOI: 10.1038/s41598-020-77910-5
|View full text |Cite
|
Sign up to set email alerts
|

Serotonin receptor 5-HT7 in Drosophila mushroom body neurons mediates larval appetitive olfactory learning

Abstract: Serotonin (5-HT) and dopamine are critical neuromodulators known to regulate a range of behaviors in invertebrates and mammals, such as learning and memory. Effects of both serotonin and dopamine are mediated largely through their downstream G-protein coupled receptors through cAMP-PKA signaling. While the role of dopamine in olfactory learning in Drosophila is well described, the function of serotonin and its downstream receptors on Drosophila olfactory learning remain largely unexplored. In this study we sho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 72 publications
0
14
0
Order By: Relevance
“…The lack of serotonergic neuron in the larval mushroom body, however, does not suggest that serotonin plays no role in learning and memory at larval stage. Recently, a serotonin receptor, 5-HT7, was found expressing in the mushroom body of Drosophila larvae, which was shown to mediate the associative olfactory appetitive learning and memory ( Huser et al, 2017 ; Ganguly et al, 2020 ). Whether serotonin mediates the associative learning and memory for S. frugiperda in the same manner could be investigated by using molecular methods in future study.…”
Section: Discussionmentioning
confidence: 99%
“…The lack of serotonergic neuron in the larval mushroom body, however, does not suggest that serotonin plays no role in learning and memory at larval stage. Recently, a serotonin receptor, 5-HT7, was found expressing in the mushroom body of Drosophila larvae, which was shown to mediate the associative olfactory appetitive learning and memory ( Huser et al, 2017 ; Ganguly et al, 2020 ). Whether serotonin mediates the associative learning and memory for S. frugiperda in the same manner could be investigated by using molecular methods in future study.…”
Section: Discussionmentioning
confidence: 99%
“…Despite the known importance of serotonergic signaling in olfactory learning in Drosophila (Ganguly et al, 2020; Johnson et al, 2011; Keene et al, 2006; Keene et al, 2004; Krashes et al, 2007; Lee et al, 2011; Sitaraman et al, 2008; Waddell et al, 2000; Wu et al, 2011; Yu et al, 2005), the dynamics of 5-HT signaling in vivo and the mechanisms that regulate this signaling processes are largely unknown. Previously, addressing these fundamental biological questions has been difficult due to the absence of suitable tools for monitoring 5-HT dynamics in vivo with high spatiotemporal resolution.…”
Section: Discussionmentioning
confidence: 99%
“…In each hemisphere of the MB, the serotonergic DPM neuron innervates all three lobes, which has been reported to be involved in olfactory learning in both adults and larvae. (Ganguly et al, 2020; Johnson et al, 2011; Keene et al, 2006; Keene et al, 2004; Krashes et al, 2007; Lee et al, 2011; Waddell et al, 2000; Wu et al, 2011; Yu et al, 2005). However, the in vivo dynamics of 5-HT release from the DPM neuron, in responses to physiological stimuli and its regulation, are poorly understood.…”
Section: Mainmentioning
confidence: 99%
“…In fruit flies, the 5HT system participates in olfactory learning and memory ( Johnson et al, 2011 ; Sitaraman et al, 2012 ; Scheunemann et al, 2018 ; Ganguly et al, 2020 ), and a previous study suggested that 5HT signals from DPM neurons modulate the activity of the MB αβ neurons, which play a crucial role in olfactory aversive anesthesia-resistant memory formation ( Lee et al, 2011 ). The axons of DPM neurons innervate the MB lobe, in which the MBON dendrites are distributed.…”
Section: Discussionmentioning
confidence: 99%